Pengaruh Return On Asset (Roa), Return On Equity (Roe) Dan Earning Per Share (Eps) Terhadap Harga Saham The Effect Of The Influence Of Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) Againts The Stock Prices - Maharani, Laely Nadya; Toha, Akhmad; Wahjuni, Sri (University of Jember, 2019)
AbstractInvestors need to see the company's performance before making a decision on investingits funds. Companies with good performance will increase the company's value accompanied with the rise of share prices. The higher the share price, the higher the profit that shareholders gain, so this condition will be favored by the investor because the increased stock demand will raise the value of the company. There are several indicators that can be used by investors to see the company's performance, one of which is by using profitability ratio. Return on assets (ROA), return on equity (ROE) and earnings per share (EPS) are ratios that can be used by investors to measure how much the companyis able to earn profit. This study aims to determine the effect of return on assets (ROA), return on equity (ROE) and earnings per share (EPS) on share prices. The research used quantitative method with descriptive approach and the analysis used was multiple linear regression by using Analyst Statistic Program for Social Science (SPSS) 18. Population in this research was all food and beverage companies listed at Indonesia Stock Exchange period 2012-2016 as many as 14 companies, while the research sampleswere 11 companies. The sample selection technique used purposive sampling technique. The results showed that return on asset (ROA) had an effect on share prices, while return on equity (ROE) and earnings per share (EPS) had no effect on share prices.Keywords : share prices, return on asset (ROA), return on equity (ROE), earnings per share (EPS)